Barriers to stroke prevention in Atrial Fibrillation: Insights from the global anticoagulation Roundtable. (October 2022) - Barnes, Geoffrey D.; Piazza, Gregory; ,; Barnes, Geoffrey D.; Chao, Tze-Fan; Njeim, Mario; Keong Poh, Kian; Zimerman, Leandro; Piazza, Gregory
Abstract: Atrial fibrillation (AF) accounts for one-quarter of the global ischemic stroke burden. Population growth and an increasing prevalence of stroke risk factors underscores the critical need to recognize and address the worldwide crisis in underutilization of antithrombotic therapy for patients with AF. Failure to address key patient, clinician, and societal gaps in AF care will result in a worldwide increase in stroke-related morbidity and mortality while overwhelming global healthcare systems. The failure to adhere to evidence-based guideline recommendations for stroke prevention in AF reflects a critical gap in implementation of best clinical practice among providers and healthcare systems. Globally, these include inadequate provider education, limited public awareness, underdiagnosis, and underutilization of treatments, including antithrombotic therapy. In specific regions, efforts are further complicated by availability of specific medications, variation in drug metabolism across racial and ethnic populations, socioreligious considerations, and lack of universally available electronic health records. Efforts are needed at both global and regional levels to address key barriers to evidence-based care for patients with AF. Investing in clinical tools and teams that improve stroke prevention for patients with AF will likely improve population health.